Effects of Heterogeneity of Financialization on Firm Innovation: Evidence in Context of Energy Transition in Lens of Research and Development - Yu, Wenjing; Zhan, Qilin; Ameer, Waqar; Li, Lianwei; Tarczyński, Waldemar; Mentel, Urszula (Frontiers in Energy Research, 2022)
Innovation is essential to promote energy transition, reduce CO2 emissions and break resources and environmental constraints. Financialization has become an important part of firm asset portfolio. Different forms of financialization have great differences in liquidity, profitability, risk and purpose. This paper focus on the effect of heterogeneity of financialization on firm innovation to provide evidence for energy transition from the perspective of R&D with annual data of non-financial listed firms in Shanghai and Shenzhen A shares from 2009 to 2018. The Pooled Ordinary Least Square, fixed effect regression, Heckman two-stage model and instrumental variable regression are implied. The study also examines the impact of agency conflict on the relationship between the heterogeneity of financialization and firm innovation. The results show that: first, there is heterogeneity in financialization, with different motives and influences on firm innovation. Second, transaction-oriented financialization can significantly improve firm innovation, while there is a negative correlation between investment-oriented financialization and firm innovation. Finally, the existence of two types of agency conflict not only weakens the role of transaction-oriented financialization in promoting firm innovation, but also intensifies the ‘crowding-out’ effect of investment-oriented financialization. Firms should allocate financialization types rationally under effective supervision and incentives to achieve innovation and energy transition goals.